Pontine lesions mimicking acute peripheral vestibulopathy - Thomke, F. (BMJ Group, 1999)
OBJECTIVES—Clinical signs of acute peripheral vestibulopathy (APV) were repeatedly reported with pontine lesions. The clinical relevance of such a mechanism is not known, as most studies were biased by patients with additional clinical signs of brainstem dysfunction. METHODS—Masseter reflex (MassR), blink reflex (BlinkR), brainstem auditory evoked potentials (BAEPs), and DC electro-oculography (EOG) were tested in 232 consecutive patients with clinical signs of unilateral APV. RESULTS—Forty five of the 232 patients (19.4%) had at least one electrophysiological abnormality suggesting pontine dysfunction mainly due to possible vertebrobasilar ischaemia (22 patients) and multiple sclerosis (eight patients). MassR abnormalities were seen in 24patients, and EOG abnormalities of saccades and following eye movements occurred in 22 patients. Three patients had BlinkR-R(1) abnormalities, and one had delayed BAEP waves IV and V. Clinical improvement was almost always (32 of 34 re-examined patients) associated with improvement or normalisation of at least one electrophysiological abnormality. Brain MRI was done in 25 of the 44 patients and confirmed pontine lesions in six (two infarcts, three inflammations, one tumour). CONCLUSIONS—Pontine dysfunction was suggested in 45 of 232 consecutive patients with clinical signs of APV on the basis of abnormal electrophysiological findings, and was mainly attributed to brainstem ischaemia and multiple sclerosis. The frequency of pontine lesions mimicking APV is underestimated if based on MRI established lesions only.